Technical and Economic Evaluation of Hybrid wind/PV/Battery Systems for Off-Grid Areas using HOMER Software - Alireza Gheiratmand; Reza Effatnejad; Mahdi Hedayati (Institute of Advanced Engineering and Science, 2016)
Incremental consumption of electrical energy, reduction of fossil fuel resources and environmental pollution problems caused by them are the main reasons, which tend the managers and officials in countries energy sector to develop use of renewable systems. In the not-too-distant future the use of renewable energy such as wind and solar will be very important and will play predominant role in economic indices of power systems. In recent years, technological advances in renewable energy and increasing price of petroleum products promote system managers to use low-cost and low-emission energy resources in form of hybrid systems and widespread propagation of electricity generation have been developed in remote areas. In Hybrid systems two or more sources of renewable energy is typically adopted, which increases the reliability of these systems. In this paper, the technical and economical consideration of a wind and solar hybrid system to supply electrical energy for a number of remote users (aid and medical emergency Shelter in Yazd) is provided. In order to investigate optimization and economic analysis of the proposed hybrid system, the HOMER software is used. The results of Simulation in HOMER software show that Solar cells and wind systems with average generation power of 896 kWh/yr. and 343 kWh/yr., consist proportion of 72 and 28 percent of the total generated energy respectively, which are dedicated to satisfy the loads